Exploring the effects of exercise on immune cell function and tumour infiltration in patients with breast cancer receiving neoadjuvant chemotherapy – a feasibility trial - Anna Ubink; Marieke R. ten Tusscher; Hans J. van der Vliet; Joeri A.J. Douma; Tanja D. de Gruijl; Hetty Bontkes; Petra Bonnet; Diede van Ens; Willemijn Hobo; Harry Dolstra; Ellis Barbé; Susanne van der Velde; et al. (Brain, Behavior, & Immunity - Health)
Pre-clinical studies have shown that exercise can decrease tumour growth through mobilisation, activation, and increased tumour infiltration of natural killer (NK) and CD8+ T cells. It is currently unclear whether this can be extrapolated to patients. Therefore, a pilot study was set up to examine the feasibility of obtaining an additional study biopsy and to generate preliminary data on the potential effects of exercise on peripheral immune cell function and tumour immune infiltration. Twenty patients with stage I-III breast cancer receiving neoadjuvant chemotherapy were included (participation rate: 27%). Patients were randomised into the intervention group receiving a six-week supervised aerobic and resistance exercise program or the control group. Blood samples and tumour biopsies were collected before randomisation and after six weeks of chemotherapy. For 8 of 20 (40%) patients, we were able to obtain and analyse biopsies at diagnosis and six-week follow-up. This showed a decrease in CD56+ cells/mm2 tumour tissue in the three patients of the control group, while it remained stable in most patients of the exercise group. Upon co-culture of peripheral blood mononuclear cells with K562 tumour cells, the exercise group showed increased expression of the degranulation marker CD107a on NK cells (β = 1038.5, 95%CI = 56.9; 2020.2, p = 0.04), and a trend towards increased tumour cell lysis in vitro (β = 18.8%, 95%CI = −3.9; 41.5, p = 0.10) compared to the control group. In conclusion, the study design was feasible with regard to the participation rate, however, revision is needed with regard to the use of a study-related biopsy prior to a sufficiently powered randomised controlled trial.